Mechanical Thrombectomy for Acute Stroke: Early versus Late Time Window Outcomes. Issue 3 (18th February 2020) - Bhan, Chantal; Koehler, Tracy J.; Elisevich, Lee; Singer, Justin; Mazaris, Paul; James, Elysia; Zachariah, Joseph; Combs, Jordan; Dejesus, Michelle; Tubergen, Tricia; Packard, Laurel; Min, Jiangyong; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Recent trials have shown benefit of thrombectomy in patients selected by penumbral imaging in the late (>6 hours) window. However, the role penumbral imaging is not clear in the early (0‐6 hours) window. We sought to evaluate if time to treatment modifies the effect of endovascular reperfusion in stroke patients with evidence of salvageable tissue on CT perfusion (CTP). METHODS: We retrospectively analyzed consecutive patients who underwent thrombectomy in a single center. Demographics, comorbidities, National Institute of Health Stroke Scale (NIHSS), rtPA administration, ASPECTS, core infarct volume, onset to skin puncture time, recanalization (mTICI IIb/III), final infarct volume were compared between patients with good and poor 90‐day outcomes (mRS 0‐2 vs. 3‐6). Multivariable logistic regression analyses were used to identify independent predictors of a good (mRS 0‐2) 90‐day outcome. RESULTS: A total of 235 patients were studied, out of which 52.3% were female. Univariate analysis showed that the groups (early vs. late) were balanced for age ( P = .23), NIHSS ( P = .63), vessel occlusion location ( P = .78), initial core infarct volume ( P = .15), and recanalization (mTICI IIb/III) rates ( P = .22). Favorable outcome (mRS 0‐2) at 90 days ( P = .30) were similar. There was a significant difference in final infarct volume ( P = .04). Shift analysis did not reveal any significant difference in 90‐day outcome ( P = .14). After adjustment; age ( P  < .001), NIHSS ( P = .01), recanalization ( P = .008), and final infarct volume ( P  < .001) were predictive of favorable outcome. CONCLUSIONS: Penumbral imaging‐based selection of patients for thrombectomy is effective regardless of onset time and yields similar functional outcomes in early and late window patients.